Institutional complexity of transboundary water, energy and food systems in the Yukon River Basin - H.M. Tuihedur Rahman; David Natcher (Environmental Development, 2026)

Assessing the agricultural production potential of northern high-latitude arable land under climate change: The case of the Northwest Territories, Canada - Lina Wu; Qi Zhao; David Natcher (Regional Environmental Change, 2026)

Bayesian network modeling of the water-energy-food nexus: the case of the Peace River Basin, Canada - Lina Wu; Qi Zhao; David Natcher (Regional Environmental Change, 2025)

Addressing gaps in integrative water-energy-food-forest (WEFF) nexus governance - HM Tuihedur Rahman; David Natcher (Environmental Science & Policy, 2025)

LCA of fishing vessels exporting fish from the Arctic - Shima Oveisi; Mazaher Moeinaddini; David Natcher (Science of The Total Environment, 2025)

Forecasting industrial induced tipping points in first nations’ land use in northeast British Columbia - Xiaojing Lu; Naomi Owens-Beek; Ryan McKay; Jim Webb; Xulin Guo; David Natcher (The Extractive Industries and Society, 2024)

The effect of information networks on the scaling out of new agricultural technologies: The case of pulse variety adoption in Southern Ethiopia - Solomon Geleta; David Natcher; Carol Jean Henry (Journal of Rural Studies, 2023)

The promise and pitfalls of community-based monitoring with a focus on Canadian examples - Abdullah Al Mamun; David C. Natcher (Environmental Monitoring and Assessment, 2023)
Community-based monitoring (CBM) is a widely used form of scientific data collection in which local community members directly participate in ecosystem research and also help the process by sharing traditional ecological knowledge and local understanding of land and resources. This paper presents a review of the challenges and opportunities associated with CBM projects in Canada and internationally. While Canadian cases are the primary focus, international examples are drawn on to provide additional context. Based on our review of 121 documents and publications, we found that CBM helps fill science research gaps by providing access to continuous data sets on the ecosystems being studied. CBM also increases the credibility of the data among users, as the community itself takes part in the environmental monitoring process. CBM supports cross-cultural learning and the co-production of knowledge by using traditional ecological knowledge with science, thereby enabling researchers, scientists and community members to learn from one another. Our review suggests that although there are multiple successes, CBM faces several challenges that constrain its progress including funding shortages, lack of support for local stewardship, and inadequate training for local users in the operation of equipment and data collection methods. Data sharing and rights on the use of data are also constraining to the long-term success of CBM programs.

Scenario planning tools for mitigating industrial impacts on First Nations subsistence economies in British Columbia, Canada - David Natcher; Naomi Owens-Beek; Ana-Maria Bogdan; Xiaojing Lu; Meng Li; Shawn Ingram; Ryan McKay; Abigael Rice (Sustainability Science, 2022)
The Montney Play Trend (MPT) is a 1090 km 2 region in northeast British Columbia that produces approximately one-third of western Canada’s natural gas output. In response to a proposed expansion of the MPT in 2016, the Government of British Columbia launched a Regional Strategic Environmental Assessment (RSEA) to identify the necessary conditions to achieve sustainable environmental outcomes. In this paper, we describe the methods and scenario planning tools that were developed to estimate how the development of the MPT might affect the subsistence economies of First Nations in the region. To demonstrate the utility of our approach, two impact assessments—Prince Rupert gas transmission pipeline and the Coastal GasLink pipeline—are presented. While no scenario can provide a definitive portrayal of exactly what will happen in the future, the tools that were co-developed are serving as an effective starting point for exploring possibilities that are at least consistent with current knowledge and can serve as a platform for collaborative learning and conflict management.

Indigenous guardians as an emerging approach to indigenous environmental governance - Graeme Reed; Nicolas D. Brunet; Sheri Longboat; David C. Natcher (Conservation Biology, 2021)
Over the past 3 decades, indigenous guardian programs (also known as indigenous rangers or watchmen) have emerged as an institution for indigenous governments to engage in collaborative environmental governance. Using a systematic review of peer‐reviewed literature for research conducted in Australia, Canada, Aotearoa‐New Zealand, and the United States, we sought to characterize the emergence of indigenous guardians in the literature and explore whether guardian approaches are representative of Indigenous approaches to environmental governance. Using a multistep relevance‐screening method, we reviewed 83 articles published since 1995, that report on, critique, or comment on Indigenous guardians. Our findings indicated that most articles on the topic were published in the last decade (88%), focused on Australia (65%), and were in a social science discipline (53%). The lead author of the majority of articles was an academic, although only half of the articles included an indigenous scholar or member of an indigenous group or organization as a coauthor. Finally, 11 articles were on research of guardian programs that were locally led and only 5 exemplified indigenous governance, based on 2 well‐known community‐based monitoring typologies. Our findings indicate that more research is required to understand the implications of current guardian programs for indigenous self‐determination, particularly when such programs are embedded in a broader western environmental governance structure.

Constraints to wildlife harvesting among aboriginal communities in Alaska and Canada - David Natcher; Shea Shirley; Thierry Rodon; Chris Southcott (Food Security, 2016)

Erratum to: The Harvest and Management of Migratory Bird Eggs by Inuit in Nunatsiavut, Labrador - David Natcher; Larry Felt; Keith Chaulk; Andrea Procter (Environmental Management, 2012)

The Harvest and Management of Migratory Bird Eggs by Inuit in Nunatsiavut, Labrador - David Natcher; Larry Felt; Keith Chaulk; Andrea Procter (Environmental Management, 2012)